HUBUNGAN PAPARAN INFODEMIC COVID-19 TERHADAP KEPATUHAN PENERAPAN PROTOKOL KESEHATAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Artini, Ni Made Kadek; Kurniati, Desak Putu Yuli (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 1 (2023): April 2023, 2023)
The outbreak of the coronavirus has had an impact on people's lives. COVID-19 not only has an impact on health but also on the economy, education, social and security. A lot of COVID-19 hoax information circulating on social media can confuse the public (infodemic). Infodemic leads to excessive information related to COVID-19 that can interfere with finding solutions and not necessarily valid information content. This study aims to determine the relationship between exposure to COVID-19 infodemic and compliance with the application of health protocols in Udayana University Medical Faculty students. This research is a quantitative analytic study with a cross sectional study approach which obtained 236 respondents. Based on the results of the study, most of the women (70.34%), reside in Denpasar (33.90%), the PSSKPD study program (38.56%) and the 2019 batch (53.81%). In addition, respondents also access information well through social media (94.07%), have a positive attitude in receiving COVID-19 information (69.92%), have a positive perception of COVID-19 information (67.37%) so that respondents were not exposed to COVID-19 hoaxes (58.47%) and respondents were obedient in implementing health procedures (75%). In this study, gender characteristics had a relationship with health care adherence (p=0.002). Likewise, access to information (p=0.026) and perception of COVID-19 information (p=0.045) had a relationship with health care compliance. Therefore, it is expected to use FK's social media to provide positive information, especially regarding COVID-19 and urge students to follow all FK's social media. Keyword : Coronavirus, Infodemic,   Health Protocol